Analysis of Factors Affecting Exchange Rate Fluctuations in Indonesia - Fitri Suci Ramadhani; Abd. Rahim; Sri Astuty; Diah Retno Dwi Hastuti; Irwandi Irwandi (International Journal of Economics and Management Sciences, 2025)
This research focuses on exchange rate fluctuations in Indonesia during the period of 2005 to 2023, influenced by various economic factors, primarily monetary policy and international trade dynamics. Exchange rate instability is a major concern because it can impact the national economy, including export competitiveness and macroeconomic stability. Consequently, the purpose of this research is to dissect the relationship between interest rates, export values, and wide money as it pertains to currency swings. This study takes a quantitative approach by analyzing the relationship between the dependent and independent variables via multiple linear regression. World Bank, International Monetary Fund, and Statistics Indonesia yearly time series data from 2005 to 2023 is used. The findings show that broad money, interest rates, and export values significantly impact the swings in the Indonesian currency. According to the findings of the multiple linear regression analysis, Interest rates and broad money have a positive and statistically significant effect on changes in exchange rates, but export values have a negative and statistically significant effect. The implications of this research emphasize the importance of appropriate interest rate policies and balanced broad money management to maintain exchange rate stability. Future researchers are advised to include global variables and more complex analysis methods.